Socio-Cultural Anthropology Today — An Overview - Boskovic, Aleksandar (Campos - Revista de Antropologia, 2005)
The paper offers a powerful deconstruction of the idea of the 'crisis' of anthropology, linking it with the fashionable way of thinking at the turn of the millennium, but very little support in practice. It is argued that this notion of 'crisis' can only be applicable to some segments of the 'Anglo-American' anthropology, not to the discipline as a whole. The paper also includes a presentation of some major theoretical debates and terminological issues present in the 19th and 20th centuries, with special focus on functionalism. One of the points made is that some of the historically popular criticisms of the discipline (for its role in the colonialism, for example) should be contextualised, as the anthropologists' role in this endeavour was actually quite limited. The paper presents five crucial sets of themes where contemporary anthropology is moving today, and where some of the most interesting research is being published. They are: the issues of identity; research on the body; consumption and material culture; studies of space and hybridity; and media and popular culture. Finally, it is claimed that social and cultural anthropology moved a long way since 1911, reaching the point where it can serve as a powerful tool for understanding all the complexities of the contemporary world.